2021
DOI: 10.31729/jnma.5838
|View full text |Cite
|
Sign up to set email alerts
|

Herlyn Werner Wunderlich Syndrome Presenting with Ischemic Stroke due to Suspected Paroxysmal Nocturnal Hemoglobinuria: A Case Report

Abstract: Paroxysmal nocturnal hemoglobinuria can rarely present as cerebral ischemia and stroke due to arterial thrombosis. However, it should be considered in a young patient with bone marrow failure features, systemic thromboses, and hemolysis. The variants of paroxysmal nocturnal hemoglobinuria pose a diagnostic challenge and hence are important to recognize. We report a case of a 28-years-old female with Herlyn Werner Wunderlich Syndrome who presented with an ischemic cerebrovascular accident, pancytopenia, hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Ischemic stroke is a common vascular brain illness with a complex pathogenesis that is significantly associated with environmental, genetic, and acquired genetic factors [ 1 , 2 ]. Ischemic stroke is a condition in which patient's cerebral arteries are blocked, resulting in a dysfunctional blood supply to the brain, leading to partial brain tissue necrosis, which severely affects the patient's neurological function [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic stroke is a common vascular brain illness with a complex pathogenesis that is significantly associated with environmental, genetic, and acquired genetic factors [ 1 , 2 ]. Ischemic stroke is a condition in which patient's cerebral arteries are blocked, resulting in a dysfunctional blood supply to the brain, leading to partial brain tissue necrosis, which severely affects the patient's neurological function [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…PNH is often misdiagnosed with different types of anemia: iron deficiency, hemolytic, megaloblastic or refractory, and sometimes as myelodysplastic syndromes [7,9]. Dr. Acharya et al reported a case of a 28-year-old Nepalese woman with Herlyn Werner Wunderlich syndrome who presented with an ischemic cerebrovascular accident, pancytopenia, hemoglobinuria, and widespread abdominal thromboses suggestive of paroxysmal nocturnal hemoglobinuria [11] A PNH clone flow cytometry test was recommended, but due to the unavailability of the test in Nepal, a nationwide lockdown due to the coronavirus pandemic, and the poor financial situation of the patient, the test could not be performed [11]. This case is just the tip of the iceberg and vividly represents the plight of patients with PNH in less resourced nations like Nepal.…”
Section: Letter To the Editormentioning
confidence: 99%